Understanding mechanisms for differential salinity tissue tolerance between quinoa and spinach: Zooming on ROS-inducible ion channels - Mohsin Tanveer; Lei Wang; Liping Huang; Meixue Zhou; Zhong-Hua Chen; Sergey Shabala (Crop Journal)
Soil salinity is a worldwide issue and a major threat to global food security. Salinity tolerance is a complex mechanism that is conferred by numerous molecular, physiological, and biochemical traits. Of critical importance are plant’s ability to regulate redox balance without compromising reactive oxygen species (ROS) signalling and maintain cytosolic ion homeostasis. In this study, the mechanistic basis of K+ retention ability in leaf mesophyll (an important but highly sensitive plant tissue) was compared between halophytic quinoa and glycophytic spinach. Phenotypic data showed quinoa outperformed spinach under 100 to 500 mmol L−1 NaCl salinity. The major difference behind this differential salinity sensitivity was a differential K+ uptake in leaf mesophyll. Electrophysiological and molecular experiments revealed that a superior ability of mesophyll K+ retention in quinoa was conferred by three complementary mechanisms: (i) an intrinsically lower H+-ATPase activity in quinoa (potentially as an energy saving strategy); (ii) reduced sensitivity of K+ transporters to ROS; and (iii) increased sensitivity of ROS-inducible Ca2+-permeable channels. Moreover, the sensitivity of K+-transport systems to ROS was further examined in NaCl-acclimated quinoa and spinach plants. The key factors differentiating between K+ retention in acclimated leaf mesophyll was associated with the reduced sensitivity and gene expression of K+-permeable outward rectifying channel (GORK), Arabidopsis potassium transporter 1 (AKT1), and high affinity potassium transporter 5 (HAK5) to additional NaCl and ROS stress, along with the upregulation of ROS scavenging system. Taken together, our results showed that the tissue-specific and ROS-specific regulation of K+ retention are important for conferring salinity tolerant at least in the halophyte quinoa.